Elaboration of a Wind Energy Potential Map in Morocco using GIS and Analytic Hierarchy Process - Elmahmoudi, F.; Abra, O. E. K.; Raihani, A.; Serrar, O.; Bahatti, L. (Engineering, Technology & Applied Science Research, 2020)
The construction of a wind power generation center starts by the selection of a suitable wind farm location. The selection includes six factors, namely wind speed, slope, land use, distance from the power lines, distance from the roads, and distance from populated areas which have been integrated into QGIS by weights calculated using the Analytical Hierarchy Process (AHP) approach. As a result of this study, the areas having very high wind potentiality have been identified and a best wind farm location map has been prepared. The map, using the overlay function in GIS, exhibits the most and least suitable areas for the location of wind farms in Morocco. The approach could help identify suitable wind farm locations in other areas using their geographic information.